Effects of short-term swimming exercise on bone mineral density, geometry, and microstructural properties in sham and ovariectomized rats - Foong, Kiew Ooi; Norsyam, Wan Mohd; Ghosh, Asok Kumar; Sulaiman, Siti Amrah; Chee, Keong Chen; Hung, Leung Kim (Elsevier, 2014)
Little information exists about the effects of swimming exercise on bone health in ovariectomized animals with estrogen deficiency, which resembles the postmenopausal state and age-related bone loss in humans. This study investigated the effects of swimming exercise on tibia and femur bone mineral density (BMD), geometry, and microstructure in sham and ovariectomized rats. Forty 3-month-old female rats were divided into four groups: sham operated-sedentary control (Sham-control), sham operated with swimming exercise group (Sham-Swim), ovariectomysedentary control (OVx-control), and ovariectomy and swimming exercise (OVx-Swim) groups. Swimming sessions were performed by the rats 90 minutes/day for 5 days/week for a total of 8 weeks. At the end of the study, tibial and femoral proximal volumetric total BMD, midshaft cortical volumetric BMD, cross-sectional area, and cross-sectional moment of inertia (MOI), and bone microstructural properties were measured for comparison. Data were analyzed using one-way analysis of variance (ANOVA). The Sham-Swim group exhibited significantly ( p < 0.05; one-way ANOVA) greater values in bone geometry parameters, that is, tibial midshaft cortical area and MOI compared to the Sham-control group. However, no significant differences were observed in these parameters between the Ovx-Swim and Ovx-control groups. There were no significant differences in femoral BMD between the Sham-Swim and Sham-control groups. Nevertheless, the Ovx-Swim group elicited significantly ( p < 0.05; one-way ANOVA) higher femoral proximal total BMD and improved bone microstructure compared to the Ovx-Sham group. In conclusion, the positive effects of swimming on bone properties in the ovariectomized rats in the present study may suggest that swimming as a non- or low-weight-bearing exercise may be beneficial for enhancing bone health in the postmenopausal population.